Timely Diagnosis of Histoplasmosis in Non-endemic Countries: A Laboratory Challenge - Buitrago, María José; Martín-Gómez, M. Teresa (Frontiers in Microbiology, 2020)
Human histoplasmosis is a fungal infection caused by the inhalation of microconidia of the thermally dimorphic fungi Histoplasma capsulatum. Autochthonous cases of histoplasmosis have been diagnosed in almost every country, but it is considered an endemic infection in specific areas of the world. Many of them are popular travel destinations or the source of migratory movements. Thus, the vast majority of the registered cases in non-endemic countries are imported. They correspond to people having been exposed to the fungus in endemic locations as immigrants, expatriates, transient workers or tourists, with reported cases also associated to organ donation. Misdiagnosis and delays in initiation of treatment are not uncommon in cases of imported histoplasmosis. They are associated to high fatality-rates specially in patients with compromised cellular immunity in which progressive disseminated forms develop. The diagnosis of this infection in non-endemic countries is hampered by the lack of clinical suspicion and a dearth of available diagnostic tools adequate to offer rapid and accurate results. Non-culture-based assays such as nucleic-acid amplification tests present as a suitable alternative in this situation, offering improved sensitivity and specificity, shortened turnaround time, and increased biosafety by avoiding culture manipulation. In non-endemic regions, molecular techniques are being used mainly in laboratories from countries that have registered an increase in the incidence of imported cases. However, the number of published techniques is limited and lack consensus. Efforts are currently under way to standardize nucleic acid amplification-based techniques for its implementation in areas registering a rising number of imported cases.